2009
DOI: 10.1021/ja9020827
|View full text |Cite
|
Sign up to set email alerts
|

Directed Assembly of PEGylated-Peptide Coatings for Infection-Resistant Titanium Metal

Abstract: Appropriate surface chemistry between a material and its surrounding biological environment is crucial to the eventual integration and performance of any implant, whether metal, plastic, or ceramic. A robust peptide-based coating technology capable of easily modifying the surface of titanium (Ti) metal through noncovalent binding is described. A short peptide possessing affinity for Ti was identified using a phage display screening process and subjected to an amino acid substitution exercise using solid-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 53 publications
1
118
0
Order By: Relevance
“…Thus, different attempts have been made to reduce not only microbial adhesion but also the deposition of host components or the occurrence of thrombosis. To do so, a peptide-based coating technology was proposed to modify the surface of Ti metal through noncovalent binding (258). In that study, a peptide (SHKHGGHKHGSSGK) possessing affinity for Ti was identified and coated with a pegylated analogue that efficiently blocked adsorption of fibronectin and S. aureus adhesion (258).…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, different attempts have been made to reduce not only microbial adhesion but also the deposition of host components or the occurrence of thrombosis. To do so, a peptide-based coating technology was proposed to modify the surface of Ti metal through noncovalent binding (258). In that study, a peptide (SHKHGGHKHGSSGK) possessing affinity for Ti was identified and coated with a pegylated analogue that efficiently blocked adsorption of fibronectin and S. aureus adhesion (258).…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…To do so, a peptide-based coating technology was proposed to modify the surface of Ti metal through noncovalent binding (258). In that study, a peptide (SHKHGGHKHGSSGK) possessing affinity for Ti was identified and coated with a pegylated analogue that efficiently blocked adsorption of fibronectin and S. aureus adhesion (258). Another group used lysozyme immobilized on polyethylene glycol monomethacrylate (PEGMA) to coat stainless steel surfaces and demonstrated that bacterial adhesion and albumin adsorption were reduced (259).…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…The peptides contained several HKH motifs that show specific binding with high affinity to titanium surfaces. The resulting surfaces showed reduced protein and bacterial adhesion [41].…”
Section: Protein-and Microorganism-repellent Coatingsmentioning
confidence: 99%
“…One approach to overcoming the problems mentioned above is to covalently bond a biocidal molecule to the surface of an implant. For titanium, linkages reported include diphosphonic acid (Danahy et al, 2004), plasma animation (Puleo et al, 2002), silanisation (Wojcik and Puleo, 1997;Antoci et al, 2007d;Sechi et al, 2007), photopolymerisation (Lawson et al, 2007), p-nitrophenyl chloroformate treatment (Mikulec and Puleo, 1996) and PEGylation (Khoo et al, 2009). This type of surface would prevent bacterial attachment and therefore block biofilm formation.…”
Section: The Need For Implant Tethered Antibioticsmentioning
confidence: 99%